with contributions by T.A. Holland and Augusta McMahon, Old Babylonian Public Buildings in the Diyala Region - Hill, Herold D. (1990)
Part I: Excavations at Ishchali (p.89-98, figs.25-27 epigraphic material); Part II: Khaf?jah Mounds B, C, and D (pls.49-50 photo of Foundation Cylinder Kh.IX:67)